(untitled) (European Journal of Marketing and Economics, 2025)
Modern companies operate under conditions of permanent change. A changing organization must be accompanied by changing - developing people. Therefore, if the development is imperative, the question is who has responsibility for it, is it the organization that makes human resources its strategic resource, or is it the employees who, in times of change, redefine the relation to the work. The answer to that question is not conclusive; therefore the article presents a dialectical approach to the responsibility for professional development, which may be located on the side of the organization, the employee or be the result of cooperation between these entities. Based on the results of own research conducted in Poland, a comparison was made of the locus of responsibility for development in the perspective of the organization and employees. The analysis was based on the results of own research conducted in Poland in 2015 on a representative sample of 289 companies and 2,274 employees (The project was funded from means of the National Science Centre conferred on the basis of the decision No DEC-2013/09 / B / HS4 / 02722). The results of the research allowed for a comparative analysis of the prospects of companies surveyed, and identification of discrepancies in this regard. This knowledge can provide guidance for the design of systems of human resources management in order to increase their effectiveness by matching organizational solutions to the expectations of employees.